Β-Elemene suppresses tumor growth of diffuse large B-cell lymphoma through regulating lncRNA HULC-mediated apoptotic pathway. Issue 2 (28th February 2020) - Hu, Tonglin; Gao, Yu
Abstract: Background: Diffuse large B-cell lymphoma (DLBCL) is considered the most common aggressive subtype of lymphoma. A number of DLBCL patients fail to achieve a response to currently available therapies or develop resistance. β-Elemene is derived from herb Curcuma wenyujin, and exhibits anti-tumor activity in both solid and non-solid tumors through modulating several molecular signaling pathways. We aimed to explore the role of β-elemene in DLBCL treatment and elucidate the involved mechanism. Materials and methods: Cell viability, apoptosis and expressions of related proteins were assessed and in vivo study were performed to determine the tumor suppressive effect of β-elemene and explore the molecular mechanisms. Results: β-Elemene significantly suppressed the viability of DLBCL cells, and β-elemene down-regulated the lncRNA HULC expression and regulated key pro-apoptotic and anti-apoptotic proteins to induce significant apoptosis of DLBCL cells. HULC overexpression could decrease the β-elemene induced apoptosis, while HULC knockdown increased the apoptosis in DLBCL cells. In vivo study further confirmed that β-elemene could suppress the growth of DLBCL xenograft and regulate the HULC expression and the critical proteins of the apoptotic pathway. Conclusion: β-Elemene performs as a tumor suppressor and modulator of HULC-mediated apoptotic pathway in DLBCL and will be an alternative candidate for clinical application.